OURIST DESTINATIONS AND DISEASE: VIETNAM’S TOURISM INDUSTRY AND THE SARS CRISIS - HENDERSON, JOAN C (ASEAN Journal on Hospitality and Tourism, 2007)
Tourism crises are becoming increasingly common, triggered by events within and outside the industry. Understanding the crisis process and managing it effectively are thus important issues for those involved in tourism. Vietnam confronted one such crisis in 2003 when the Severe Acute Respiratory Syndrome (SARS) virus, which affected a number of countries in the region, was discovered in Hanoi. Fears of the disease led to a sudden fall in tourist arrivals and prompted a response from the industry in the areas of health and safety, finance, human resources and marketing. Management of the crisis appeared generally successful, although recovery was aided by wider developments. Information obtained from interviews with industry representative is presented and a crisis management campaign model is proposed to help assist in future crises which seem inevitable in the modern world.